Inflation and growth in Latin America - Baer, Werner; Kerstenetzky, Isaac (New Haven ; Yale University Press, 1970)
Although the theme of the conference was inflation and growth, many other aspects of development are related to this central theme, and the discussion occasionally wandered off into most interesting, but not necessarily closely related topics.
Includes bibliographical references.
osc 03/05/2018
Loans
Keywords: Inflation (Finance); Latin America